2011
DOI: 10.1002/iub.481
|View full text |Cite
|
Sign up to set email alerts
|

Lung vascular targeting through inhalation delivery: Insight from filamentous viruses and other shapes

Abstract: SummarySystemic delivery of therapeutic agents via inhalation of particulates remains an attractive, noninvasive means of administration due to the possibilities of high bioavailability and high patient compliance. Optimization of particle shapes and particle properties for deep lung deposition after inhalation continues to be one of the key challenges. Here, we review several aspects of nanoparticle design for deep lung deposition as well as the nature and extent of translocation through the air-blood barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…There are three main mechanisms by which particles deposit in respiratory tract: impaction, sedimentation and/or diffusion 6 . Particles deposit in the mid and deep lung regions when the aerodynamic particle size is ≤5µm 1,6,7 , which is where nanoparticles have a niche in advanced pulmonary drug delivery. Nanoparticles can be used for targeted delivery 8 , sustained delivery and deep lung delivery of drugs and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main mechanisms by which particles deposit in respiratory tract: impaction, sedimentation and/or diffusion 6 . Particles deposit in the mid and deep lung regions when the aerodynamic particle size is ≤5µm 1,6,7 , which is where nanoparticles have a niche in advanced pulmonary drug delivery. Nanoparticles can be used for targeted delivery 8 , sustained delivery and deep lung delivery of drugs and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, spherical carriers smaller than tens of nanometers can be injected using diverse vascular, muscular and dermal routes, whereas carriers larger than few hundred nanometers can be administered via large vessels and airways [173177]. The shape further modulates delivery: for example, non-spherical carriers circulate longer and avoid uptake by defense cells more effectively than spherical counterparts, whereas propeller-shape nanoparticles reach more deep deposition sites in the airways than spherical ones [81,178]…”
Section: Control Of Dds Targetingmentioning
confidence: 99%
“…However, as the literature has reported that mucoadhesive particles might inhibit the mucociliary clearance via increasing the viscoelastic properties of the mucosal fluids, there is a deep concern for the time period of mucus renewal and side effects of inhibiting mucociliary clearance [55]. In addition to mucociliary clearance, another important clearance mechanism in the airway is the rapid macrophage uptake of inhaled particulates [48,[56][57][58]. For macrophage uptake, the preferred geometric size range of particles is overlapped with most respirable aerodynamic size range of 0.5-5 µm [59,60].…”
Section: Hydrogelsmentioning
confidence: 99%